Covenants without swords : idealist liberalism and the spirit of empire - Morefield, Jeanne, 1967- (Princeton University Press, 2005)
Covenants without Swords examines an enduring tension within liberal theory: that between many liberals' professed commitment to universal equality on the one hand, and their historic support for the politics of hierarchy and empire on the other. It does so by examining the work of two extremely influential British liberals and internationalists, Gilbert Murray and Alfred Zimmern.